Los títeres como estrategia metodológica para disminuir las conductas disruptivas en los niños del primer año de la escuela de educación básica 18 de Noviembre de la cuidad de Loja, en el período académico 2019-2020 - Carrión Macas, Jenniffer del Cisne (2021)
The research titled PUPPETS AS A METHODOLOGICAL STRATEGY TO REDUCE DISRUPTIVE BEHAVIORS IN CHILDREN OF THE FIRST YEAR OF THE BASIC EDUCATION SCHOOL NOVEMBER 18, LOJA CITY, IN THE 2019-2020 ACADEMIC PERIOD. Its general objective was to determine how puppets reduce disruptive behaviors in first year children of the 18 de Noviembre school in the city of Loja in the academic period 2019-2020. In the literature review, issues related to disruptive behaviors were addressed and the puppets. In the development of the research, the following methods were used: analytical-synthetic, inductive-deductive, scientific, and descriptive statistics. To obtain information, a teacher survey was conducted, the observation guide used to determine disruptive behaviors is adapted based on the Instrument to evaluate behavior disorders by Isabel C. Puerta and the Eyberg Inventory of behavior in children of the authors García, Calzad and Eybergentro, which allows evaluating the normality or maladjustment of the child's behavior according to its development and the scientific basis contained in the theoretical framework. The investigated sample comprised 2 teachers and 23 children. In the diagnosis at the level of physical and gestural aggressive behaviors, they were evidenced with a high problem index. In the pre-test it was evidenced that 83% of the investigated population present aggressive verbal behaviors in relation to screaming and physical aggressive behaviors, 89% in relation to destruction and aggression of objects, 61% with pinching. To reduce disruptive behaviors in children, a playful activity guide based on puppets was designed and applied, which lasted 2 months. Once the alternative proposal was applied, the data obtained in the post-test was that 13% of the population presented aggressive verbal behaviors in relation to shouting and aggressive physical behaviors, 9% of the population still manifested aggression and destruction of objects and pinching it was evidenced that it decreased in its entirety. For which, in general, it is concluded that a wellplanned activity guide helps to reduce this type of behavior in children, also taking into account the support of the teacher and parents throughout the educational process